Substance Abuse Effect on Cognitive Ability of Selected Youngsters Studying in Gwadabawa, Sokoto State, Nigeria - Tambari, Ishaka; Aliyu, Mustapha; Sulaiman, Bello (ALSYSTECH Journal of Education Technology, 2024)
Substance abuse is among the major issues affecting schools and education in Nigeria. Many substances affect the mind and whole body of youngsters negatively leading to hospitalizations, school drop-outs, absenteeism and other effects that affect education at whole. The objective of this study was to assess the effect of substance abuse on cognitive potential of some schooling youngsters in Gwadabawa, Sokoto State Nigeria. 15 young people that abuse substances and are attending schools, and 15 normal people in Gwadabawa, Sokoto state, Nigeria were recruited in this work and were assessed with Montreal cognitive Assessment standard methods to evaluate the cognitive domain of the participants. The result reveals substance abusers scored 357 ± 7.0, while 396.0 ± 10.0 was scored by non-substance abusers; indicating that substance abusers show comparatively lower cognitive ability compared to the control youngsters enrolled in this work. The results indicate that the substances been abused by the young people reduce their cognitive ability (a prelude of cognitive domain of the participants of the study) and in turn could inflict their academic performances as well. Thus, it is pertinent to help young ones shun substances through awareness creation, counselling, strict laws, drug education and relations.